Analysis of Weld Induced Distortion of Butt Joint using Simulation and Experimental Study / Mohd Shahar Sulaiman ...[et al.] - Sulaiman*, Mohd Shahar; Manurung, Yupiter HP; Graf, Marcel; Bauer, Alexander (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper focuses on investigation of welding distortion that occurred due to GMAW process which can adversely affect the dimensional accuracy and aesthetical value of the welded structure. Distortion can lead to production delay and costly remedial work. Based on this fact, it is necessary to predict the welding distortion in advance in order to produce high quality welded parts and thus to reduce production cost. In this study, the welding distortion induced in butt joint with thickness of 4 mm was simulated using Finite Element Method (FEM) software Simufact.Welding Version 5. The welding deformation was computed based on non-linear thermo-elastic-plastic numerical analysis. Low carbon steel material was employed for the simulation and experimental study. A series of experiments using fully automated welding process were carried out for verification purpose in order to measure the distortion. By comparing the results between simulation and experiment, it was found out that a good agreement was achieved and fast solution analysis time was provided in predicting weld induced distortion.